Innovative plAnt Protein fibre and Physical activity solutions to address poor appEtite and prevenT undernutrITion in oldEr adults – APPETITE - Volkert, Dorothee; Corish, Clare A.; Dardevet, Dominique; De Vito, Giuseppe; Guillet, Christelle; Bader-Mittermaier, Stephanie; Robinson, Sian; Roche, Helen M.; Sayer, Avan A.; Visser, Marjolein (Nutrition Bulletin, 2021)
Older adults with poor appetite are at higher risk of undernutrition due to the role of appetite as a key driver of food intake. Dietary protein and fibre are critical nutrients in this population, and enhancing their intake is vital to preventing undernutrition and maintaining organ function and health. In APPETITE, a transdisciplinary consortium of experts from eight institutions in six European countries will collaborate to design potentially effective interventions to enhance protein and fibre consumption of community-dwelling older adults with poor appetite, thereby addressing undernutrition through a targeted nutrition- and physical activity-based strategy. Older adults with poor appetite will first be evaluated using a mixed-methods approach to gain insights into their nutritional and behavioural preferences. Working with this target group, innovative, acceptable and affordable food products will be developed that combine several domestic plant proteins and dietary fibres. Mechanistic insights will be gained by examining the impact of selected products and physical activity on digestibility, amino acid bioavailability and whole-body protein metabolism. In a multi-country, randomised controlled intervention trial, the impact of two new food products, provided as part of a personalised diet, a physical activity programme, and their combination will be determined. APPETITE will improve our understanding about plant-based protein and fibre products and their metabolic and clinical effects. It will create new knowledge about how these products can be combined in a whole-diet approach, together with physical activity and regular social contacts, to overcome undernutrition and to contribute to a better quality of life for older Europeans.
CRIS-Team Scopus Importer:2021-11-26
Keywords: appetite; fibre; malnutrition; older adults; personalised nutrition; plant protein; undernutrition